Do we need mother tongue language maintenance in Aceh? Voices from the school setting - Mulyani Mulyani; Ika Kana Trisnawati; Syarfuni Syarfuni; Mulyadi Syahputra; Sariakin Sariakin; Rosdiana Rosdiana (Studies in English Language and Education, 2024)
There is a possibility that the Acehnese language and other locally used languages in Aceh Province could become threatened if the locals do not make efforts to maintain them. This study aims to explore teachers perspectives on maintaining the Acehnese mother tongue in schools. Employing a mixed-methods research design, data was collected through surveys and semi-structured interviews. The survey was distributed via Google Forms to 217 schoolteachers selected through voluntary sampling in Aceh, while interviews were conducted with seven teachers who willingly participated in the study. The results indicate that most teachers agree on maintaining the use of local languages in schools. However, language maintenance may face challenges e.g., globalization, family role, and youth attitude. Hence, teachers recommend that schools should actively promote the use of local languages by designating a special day for celebrating their use and incorporating the languages into local content lessons. This study intends to provide insightful recommendations for policy development regarding the maintenance of local languages in the school setting, particularly in Aceh. It also suggests educational implications, such as integrating these languages into formal schooling and developing educational resources to enhance their use in schools. Furthermore, future research could focus on documenting and preserving local languages, as well as implementing language immersion programs aimed at preserving local languages in Aceh.